Situation Report: Hungary, 25 February 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Thatcher Visit to Hungary / by Alfred Reisch Hungarian-British Economic and Cultural Ties / by Alfred Reisch Yugoslav Journalists Disagree over Hungary's "Economic Miracle" / by Slobodan Stankovic Meat Prices / by Alfred Reisch Riddles of the 1984 Budget and Plan / by Tibor Kovacsy Unorthodox Hungarian Art Exhibit Closed / by Eva Lengyel